PENGARUH STRATEGI (CTL) OLEH GURU PENDIDIKAN AGAMA KRISTEN TERHADAP KEAKTIFAN BELAJAR SISWA KELAS V DAN VI DI SD NEGERI 173366 PARMONANGAN TAHUN AJARAN 2021/2022 - Hesron Situmeang (Jurnal Pendidikan dan Kebudayaan (JURDIKBUD), 2023)
Abstract, The purpose of this study was to determine the effect of Strategy (CTL) by Christian Religion Teachers on the learning activity of Grade V and VI students at SD Negeri 173366 Parmonangan for the 2021/2022 Academic Year. The method used in this research is inferential statistical method. The population is all students of grades V and VI at SD Negeri 173366 Parmonangan with a total of 225 people and a sample of 90 people. Data was collected using a closed questionnaire consisting of 35 items compiled by the author himself. The results of the data analysis show that there is a positive and significant effect of Strategy (CTL) by the Christian Religion Teacher on the learning activity of Class V and VI students at SD Negeri 173366 Parmonangan for the 2021/2022 Academic Year with the following data analysis: 1) Test the analysis requirements: a) A positive relationship test obtained rxy = 0.66> rtable = 0.207 b) A significant relationship test obtained tcount = 3.52> ttable = 1.671 thus there is a significant relationship between variable X and variable Y. 2) Test the effect : a) Test the regression equation, the regression equation is obtained with the regression coefficient of determination (r2) = 0.43% and Fcount > Ftable, namely 91.25 > 1.25, thus H0 is rejected and Ha is accepted. That is, there is a positive and significant influence between the effect of strategy (CTL) and the learning activity of class V and VI students of SD Negeri 173366 Parmonangan 2021/2022.